The Effectiveness of Theory of Mind Training On the Social Skills of Children with High Functioning Autism Spectrum Disorders - ADIBSERESHKI, Narges; NESAYAN, Abbas; ASADI GANDOMANI, Roghayeh; KARIMLOU, Masood (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Adibsereshki N, Nesayan A, Asadi Gandomani R, Karimlou M. The Effectiveness of Theory of Mind Training On the Social Skills of Children with High Functioning Autism Spectrum Disorders. Iran J Child Neurol. Summer 2015;9(3):40-49. Abstract Objective Children with Autism Spectrum Disorders (ASD) tend to have problems in establishing and maintaining their social relationships. Some professionals believe this social impairment is the result of deficit in Theory of Mind (ToM). This study was conducted to explore the effectiveness of ToM training on such children. Materials & Methods A quasi-experimental method, pre- test, post-test with control group was used. The sample included of 12 girls and 12 boys with High Functioning Autism Spectrum Disorders (HFASD). Two instruments were used as follows: the Theory of Mind test and the social skills questionnaire (1). The samples were randomly placed in the experimental and control groups. The experimental groups had 15 sessions of ToM training and the control groups had just regular school program. Results The data were analyzed by Kolmogorov-Smirnov, independent t- and twoway- variance tests. The scores for social skills in the experimental group were significantly more than the control group. Conclusion ToM training might improve the social skills of children with autism spectrum disorders.